Igrejas, conventos, cemitérios: o lugar dos mortos configurando a paisagem urbana e arquitetônica da cidade de Marechal Deodoro, Alagoas - Magalhães, Ana Cláudia Vasconcellos (2018)
The genesis of the Brazilian colonial cities has been studied under several aspects, especially about the economic dynamics underlying the movements on occupation and settlement on the territory. Recently, a new generation of researchers has focused on the role of religious events, especially those related to funerary culture. Researching that have considered the dynamics linked to Death as spatial agents, recognize that, although it seems contradictory, it was a great contribution of the vitality of urban daily life till at least until the nineteenth century, when emerged a new way of dealing with the place of the dead in the built and cultural landscape of cities. In the light of this context, this thesis explored and discussed how, in the city of Marechal Deodoro, located in Alagoas, Brazil, urban requirement regarding funeral practices were met, a fundamental condition for the population to maintain its status as an inhabited space. It is considered that these practices were part of the whole social extracts, which, organized in confraternities, were responsible for the construction and maintenance of the spaces that the canonical legislation of the epoch considered appropriate for the burials: convents, churches, chapels, churchyard. The culture of the Death come out in the city through small and great urban and architectural gestures such as spaces built for the burials; network of streets organized according function of processions, cortege, funerary routes, religious devotions. From the middle of the nineteenth century, different ways of dealing with old beliefs were defined, and the new place dedicated to the dead as the Public Cemetery, have established a distinctive, and at a time, conflicting relationship between the a kind of territory of Death and the inhabitants. On the whole, the city, in its built dimension and its symbolic dimension, begins to reflect this other reality.